ANALISIS YURIDIS HUKUMAN BAGI PELAKU TINDAK PIDANA PERDAGANGAN ORANG: (Studi Kasus Putusan Nomor 1318 Pk/Pid.sus/2023) - Simbolon, Winda; Hotdeliana Simanjuntak, Sarida; Setyawan, Iwan; Suranta Sembiring, Jenda (Veteran Law Review, 2025)
This study aims to examine the sentencing of human trafficking perpetrators based on the Supreme Court Decision No. 1318 PK/Pid.Sus/2023. Despite existing laws, human trafficking remains prevalent in Indonesia. The objective of this research is to understand how the Indonesian judicial system imposes criminal sanctions and to analyze the factors that influence the judges' decisions. This is normative legal research using statutory and case approaches. The case analyzed involves a defendant convicted under Article 2(1) in conjunction with Article 48 and Article 4 in conjunction with Article 48 of Law No. 21 of 2007 on the Eradication of Human Trafficking. The perpetrator was sentenced to seven years of imprisonment, a fine of IDR 120,000,000.00, and restitution of IDR 117,000,000.00 to the victim. The petition for judicial review was rejected by the Supreme Court due to the failure of the new evidence to qualify as novum. The findings show that although legal provisions are in place, obstacles persist in ensuring a deterrent effect. This study highlights the need to evaluate sentencing effectiveness and strengthen law enforcement in handling human trafficking cases.